Work Family Sinergy : Anteseden Dan Konsekuen - Wisnu Prajogo; Maria Pampa Kumalaningrum (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
This research is aimed to examine the influence of family role conflict  and family role ambiguity to work-family sinergy, the influence of work-family sinergy to life satisfaction and performance, and the influcene of life satisfaction to performance.269 employees from various organization participated in this research. This research has several findings. Family role conflict does not influence  work-family sinergy, Family role ambiguity has negative influence to work-family sinergy, Work-family sinergy has positive influence to life satisfaction, Life satisfaction does not influence performance, Work-family sinergy has positive influence to performance.